Bibliometric Insights into the Evolution of Health Information Systems and Telemedicine Research - Judijanto, Loso (Eastasouth Institute, 2024)
This bibliometric study provides a comprehensive analysis of the research landscape in Health Information Systems (HIS) and Telemedicine, elucidating key trends, influential factors, and thematic clusters shaping the field's evolution. Through systematic data collection and analysis of nearly a thousand scholarly articles, this research offers insights into publication output, citation patterns, collaboration networks, and thematic areas within HIS and Telemedicine research. Thematic network and temporal analyses reveal distinct clusters focusing on telehealth, HIS implementation, advanced telemedicine technologies, and contextual factors influencing telemedicine adoption. Highly cited papers and author collaboration networks further underscore seminal contributions and research clusters within the field. Overall, this study contributes to a deeper understanding of the current state of HIS and Telemedicine research, informing strategic initiatives for future advancements in healthcare technology and delivery.